How students with different learning styles collaborate in an online learning environment - Yang, Bo (Kansas State University, 2007)
This naturalistic case study was designed to provide descriptive data to examine the possible role of student learning styles in their collaborative participatory behaviors in an online text-based learning environment; and whether the technology-rich environment that promotes collaborative, project-based learning can have an effect on learners’ participation behavior from the point of view of learning styles. In this study, graduate and advanced undergraduate students’ discussion posts, project reports, reflections, and archived chat records were carefully analyzed. The research results indicated that, in an online collaborative learning environment participants were observed to use the Convergent, Divergent and Accommodating learning styles more often than Assimilating learning styles. Indeed, participants with the Assimilating learning style did not show a positive attitude towards online collaboration. Moreover, students who took a leadership role had their learning style kite shape close to the Concrete Experience learning mode; others who were more supportive had their kite shape close to the Reflective Observation “watching”; and those usually took both a leadership role and a supportive role and were comfortable with a variety of learning modes had their kite shape balanced along two or more dimensions of the learning cycles. The discussion of identified themes in this study is related to Kolb’s Experiential Learning Theory framework. The study provides extended implications and suggestions for future research.
Keywords: Collaborative learing; Learning style; Online learning; Computer-mediated communication; Education, Curriculum and Instruction (0727); Education, Technology (0710)